Creation of Cultural Local Wisdom-Based Picture-Science Stories Application for the Introduction of Scientific Literacy for Early Childhood - Eliza, Delfi; Mulyeni, Trisna; Budayawan, Khairi; Hartati, Sri; Khairiah, Fisna (JOIV : International Journal on Informatics Visualization, 2024)
This article aims to explain the design, development, implementation, and evaluation of the Picture Science Story (CSB) application integrated with local wisdom based on an Android application for early childhood. This application can be used with a touch screen. The aim of making this application is to introduce the science process skills and local wisdom to the children. The research method used was R and D. The initial stage of developing the CSB prototype model was to conduct the needs analysis, child characteristics, and curriculum analysis. Then, the design, development, implementation, and evaluation of the CSB application were carried out. The application used a layered platform. Many experts from different fields were involved in the design process: graphic design experts to create images, multimedia experts to create applications, and teachers for the science material. The CSB prototype design was validated by material, media, and user experts, namely Al-Huffaz Kindergarten teachers and children. The participants in this research were 13 Alhufazh Kindergarten students. A questionnaire was given to get a response from the teachers, consisting of aspects of understanding multimedia, function, and configuration. The average score of the teachers’ responses was 92%. Meanwhile, the average score of children's responses was 95%. Based on the results of validation and trials, it was found that the CSB application integrated with local wisdom based on an Android application was valid, effective, and practical for early childhood. The suggestions from users require multidisciplinary knowledge in designing picture-science stories based on Android applications. Then, the feedback addressed the importance of using the Science Story Creation prototype and integration of the Local Wisdom of Minangkabau Culture to introduce Early Childhood Science Literacy.